Makromolekul dari Mikroalga Spirulina platensis - Ahmad Fauzan Lubis; Ahyani Ridhayani Lubis (PAKIS JOURNAL INSTITUTE, 2023)
Spirulina platensis is known to have various benefits because it contains various compounds, some of which are reported to have immunomodulatory, antioxidant, anticancer, antitumor, antiviral, anti-inflammatory, cholesterol-lowering, anti-rust, hepatitis prevention, metal chelating and blood formation stimulation activities. Therefore, to determine the nutritional composition (macromolecular content) of Spirulina platensis as a food ingredient, it is necessary to analyze these components. This study aims to measure the growth pattern and the content of macromolecular components found in Spirulina platensis. The method in this study included preparation of Spirulina platensis samples (Spirulina platensis culture), optical density (OD) measurements, and the parameters tested were proximate analysis (AOAC, 2005) to determine protein content, fat content, ash content, moisture content, and The results obtained from this study were that Spirulina platensis underwent 4 growth phases, namely the log phase (1-4 days), the log phase (5-10 days), the stationary phase (11-17 days) and the death phase starting in 18th day. Spirulina platensis in the log phase had a higher macromolecular content than the stationary phase with protein (12.54%), carbohydrates (22.46%) in the log phase, protein (8.64%), carbohydrates (13.36%) in the stationary phase, while the fat content was the same at 4%, the high ash content was the log phase (56%), and the stationary phase (68%).